The results of screening examinations of breast cancer conducted from 2004 to 2005 in Sierpc poviat - Nowicki, Andrzej; Miłecka, Agnieszka (Contemporary Oncology/Współczesna Onkologia, 2007)
Background : Breast cancer is one of the most common malignant neoplasms among women in Poland. 11733 new cases were registered in 2003. Well organized screening examinations are the most effective method of fighting against breast cancer. Aim of study : The main objective of this work was a preliminary analysis of a prophylactic examination programme for breast cancer in Sierpc district performed by the Independent Unit of Public Health Care Centres in Sierpc during the period of 2004 to 2005. Material and methods : The research was performed based on retrospective analysis of files obtained from the Department of Radiology of the Independent Unit of Public Health Care Centres in Sierpc. Prophylactic examination for detection of breast cancer includes physical examination of the breast as well as mammography. Results : The research includes 1291 women, most of them at age 50-55 years (57.1 years on average). City residents represent the biggest group of women. Nearly half of women had their first menstruation at the age of 14 to 15 years. The last menstruation occurred at age between 46 and 50 years old most frequently. The average number of labours was 2.3 and 2.5 during the analyzed period. The first labour occurred most frequently in women at the age of 21 to 25 years old. Most of the women never took previously and still do not take hormonal medicines. 80% of women have done breast self examination but over half of them (60.8%) did it occasionally. Breast examination done by a gynaecologist was performed in 22% of women during the last year. Breast cancer did not occur among family members in most of the analyzed women. Breast pain was the most frequent complaint. Over half of women (64.6%) previously underwent mammography. The biggest group among them (31.1%) includes women who had mammography between 2003 and 2004. Adipose-glandular breast texture was detected in near half of women (43.5%). The result of mammography was normal in most analyzed women (87.1%). A potentially malignant lesion according to the BIRADS scale was shown in four (0.3%) women. Conclusions : 1291 prophylactic mammographies were performed in 22.3% of women at age 50-55 years old, mainly in Sierpc district during 2004 to 2005. Suspected or potentially malignant lesions were detected in mammography in 1.4% of women. Breast cancer was diagnosed in 0.7% of the examined population.